Sphingosine-1-Phosphate Receptor Subtype 1 (S1P1) Modulator IMMH001 Regulates Adjuvant- and Collagen-Induced Arthritis - Jin, Jing; Ji, Ming; Fu, Rong; Wang, Mingjin; Xue, Nina; Xiao, Qiong; Hu, Jingpin; Wang, Xiaojian; Lai, Fangfang; Yin, Dali; Chen, Xiaoguang (Frontiers in Pharmacology, 2019)
Sphingosine-1-phosphate receptor subtype 1 (S1P1) is essential for lymphocyte egress from lymphoid organs into systemic circulation and provides a well-defined drug target for autoimmune disorders. IMMH001, also called SYL930, is a specific S1P1/S1P4/S1P5 modulator. Here, we investigated the potential therapeutic effect of IMMH001 on rheumatoid arthritis (RA). IMMH001 rendered periphery blood lymphocytes insensitive to the egress signal from secondary lymphoid organs. Importantly, in both rat adjuvant-induced arthritis and collagen-induced arthritis models, IMMH001 treatment significantly inhibited the progression of RA and RA-associated histological changes in the joints of Sprague-Dawley rats, including hind paw swelling and arthritic index, and thus reduced the pathological score. Furthermore, IMMH001 markedly decreased proinflammatory cytokine and chemokine release from the damaged joints. These data demonstrated that IMMH001 is a promising drug candidate for RA treatment.